2016
DOI: 10.1021/acs.jafc.6b00539
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant FIP-gat, a Fungal Immunomodulatory Protein from Ganoderma atrum, Induces Growth Inhibition and Cell Death in Breast Cancer Cells

Abstract: FIP-gat, an immunomodulatory protein isolated from Ganoderma atrum, is a new member of the FIP family. Little is known, however, about its expressional properties and antitumor activities. It was availably expressed in Escherichia coli with a total yield of 29.75 mg/L. The migration of recombinant FIP-gat (rFIP-gat) on SDS-PAGE corresponded to the predicted molecular mass, and the band was correctly detected by a specific antibody. To characterize the direct effects of rFIP-gat on MDA-MB-231 breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Activating macrophages and cytokines [147,148] Grifolan Grifola frondosa Activating macrophages and lymphokines [149] Lentinan Lentinus edodes T-cell-oriented adjuvant [149] PS-G Ganoderma lucidum Activating macrophages and T lymphocytes [135,136] Schizophyllan Schizophyllum commune Activating T cell, increasing interleukin and TNF-α production [150] Terpenoids…”
Section: Morchella Esculenta Morchella Conicamentioning
confidence: 99%
“…Activating macrophages and cytokines [147,148] Grifolan Grifola frondosa Activating macrophages and lymphokines [149] Lentinan Lentinus edodes T-cell-oriented adjuvant [149] PS-G Ganoderma lucidum Activating macrophages and T lymphocytes [135,136] Schizophyllan Schizophyllum commune Activating T cell, increasing interleukin and TNF-α production [150] Terpenoids…”
Section: Morchella Esculenta Morchella Conicamentioning
confidence: 99%
“…Indirectly, FIPs activate the immune system. Of the direct inhibitory effects on cancer cells, some examples include rLZ-8 promoting apoptosis by G1/S phase arrest in human glioblastoma U-251 MG cells [25] and rFIP-gat significantly inhibiting cell growth, causing cell cycle arrest at the G1/S phase, and inducing apoptosis in MDA-MB-231 breast cancer cells [7]. Previous studies have demonstrated that rFIPs (rFIP-nha from N .…”
Section: Discussionmentioning
confidence: 99%
“…FIPs regulate immunity by stimulating lymphocyte proliferation, inducing T H 1-specific cytokine synthesis (interleukin-2, interferon-γ, and tumour necrosis factor β), and inhibiting anaphylaxis [1]. The anti-tumour effects that are displayed by FIPs refer to the suppression of tumour cell proliferation, promotion of tumour cell apoptosis, the induction of tumour cell cycle arrest, and the inhibition of tumour cell migration [7,8]. FIPs have very broad potential future applications in medical care, and the anti-tumour effects in particular have attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIP-fve has anti-inflammatory effects on OVA-induced airway inflammation and reduces airway remodeling by suppressing IL-17 (12). In spite of a few studies about anti-tumor (13, 14) and immunomodulatory effects (1517), the mechanism of these activities remain unclear. The relationship between the activation of these proteins, downstream cytokine expression and physiological function represents an active line of investigation.…”
mentioning
confidence: 99%